A General-purpose Parallel and Heterogeneous Task Programming System for VLSI CAD - Huang, Tsung-Wei (Digest of technical papers - IEEE/ACM International Conference on Computer-Aided Design, 2020)
This paper introduces Taskflow to address the critical question of "How can we make it easier to implement and deploy parallel computer-aided design (CAD) algorithms on large heterogeneous nodes with high performance and simultaneous high productivity?" Parallelizing CAD is an extremely challenging job. Modern CAD applications exhibit unique computational patterns and user requirements that need very strategic decomposition to benefit from parallelism. Taskflow assists researchers and developers in the implementation complexity of parallel algorithms by introducing a new high-level programming model supported by an efficient runtime. By capitalizing on emerging parallelism comprising manycore central processing units (CPUs), graphics processing units (GPUs), and custom accelerators, Taskflow enables CAD to achieve new performance and productivity milestones that were previously out of reach.